2017
DOI: 10.1016/j.ejca.2017.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant buparlisib plus trastuzumab and paclitaxel for women with HER2+ primary breast cancer: A randomised, double-blind, placebo-controlled phase II trial (NeoPHOEBE)

Abstract: Aim The Neoadjuvant PI3K inhibition in HER2 OverExpressing Breast cancEr (NeoPHOEBE) trial evaluated the efficacy and safety of buparlisib, a pan-phosphatidylinositol 3-kinase (PI3K) inhibitor, plus trastuzumab and paclitaxel as neoadjuvant treatment for human epidermal growth factor receptor-2 positive (HER2+) breast cancer. Methods NeoPHOEBE was a neoadjuvant, phase II, randomised, double-blind study. Women with HER2+ breast cancer were randomised within two independent cohorts by PIK3CA mutation status an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 44 publications
(37 reference statements)
2
68
1
1
Order By: Relevance
“…This result is in line with a phase 2 trial that suggested that BKM‐120 in combination with paclitaxel could be an effective second‐line treatment for head and neck squamous cell carcinoma patients . However, two other trials failed to demonstrate improvement from the addition of BKM‐120 to chemotherapy in the full or in a PI3K pathway‐activated study population . Here we find for the first time that PI3K inhibitors decrease stathmin expression and phosphorylation.…”
Section: Discussionsupporting
confidence: 89%
“…This result is in line with a phase 2 trial that suggested that BKM‐120 in combination with paclitaxel could be an effective second‐line treatment for head and neck squamous cell carcinoma patients . However, two other trials failed to demonstrate improvement from the addition of BKM‐120 to chemotherapy in the full or in a PI3K pathway‐activated study population . Here we find for the first time that PI3K inhibitors decrease stathmin expression and phosphorylation.…”
Section: Discussionsupporting
confidence: 89%
“…A randomized adaptive phase II/III study (BELLE-4) suggested that addition of buparlisib to paclitaxel did not improve PFS of patients with HER2 negative advanced breast cancer [120]. In a placebo-controlled phase II trial (NeoPHOEBE), addition of the pan-PI3K inhibitor buparlisib to taxane-trastuzumab-based therapy in HER2 positive early breast cancer was revealed to be unfeasible [121].…”
Section: Pf-04691502 and Pf-05212384 (Gedatolisib Pki-587)mentioning
confidence: 99%
“…Likewise, in HER2-positive BC patients, presence of a PIK3CA-mut is associated with worse response rates to neoadjuvant treatment [62]. Phase I/II studies demonstrated the overall feasibility of combining anti-HER2 treatments with PI3Ki (Table 2) [46,[50][51][52][53][54][55][56][57][58][59]63]. A phase II study including HER2-positive, trastuzumab-resistant metastatic BC patients treated with buparlisib and trastuzumab showed an overall response rate of 10%, but grade !…”
Section: With Anti-her2 Agentsmentioning
confidence: 99%